Utilization of Fungal Treated Waste Foundry Sand in Concrete - Kaur, Gurdeep (My University, 2013)
Solid waste management has become one of the global environmental issues, as there is continuous increase in industrial by-products and waste materials. . Due to lack of land filling space and its ever increasing cost, utilization of waste material and by-products has become an attractive alternative to disposal. The beneficial use of such by-products in construction materials results in reducing the cost of construction materials’ ingredients and also helps in reducing disposal problem. Waste foundry sand (WFS) is one of such industrial by-product which could be used in construction materials. The leachate obtained from such materials may contain hazardous compounds, which may possibly effect the environment. Leaching characteristics are essential in understanding the environmental impact or toxicity, disposal and potential development of beneficial applications of WFS. This study aimed to present the utilization of fungal treated WFS in concrete. This experimental investigation was performed to evaluate the properties of M20 (31 N/mm2) Grade of concrete mixes, in which sand was partially replaced with waste foundry sand (WFS). Sand was replaced with four percentages of untreated and fungal treated WFS (0%, 10%, 15% and 20%). Fungal (Aspergillus niger and Eupenicillium crustaceum) inoculums (2%) were used for the treatment of WFS. Fungal treated WFS were utilized for the preparation of concrete. Concrete mixes were prepared with partial replacement of untreated WFS and fungal treated WFS. Compressive strength, water absorption and porosity were carried out to evaluate the properties of concrete containing untreated WFS and concrete containing fungal treated WFS at the age of 28 days. Study also included leachate analysis obtained from the concrete mixes made with fungal treated vi WFS, untreated WFS (0%, 10%, 15% and 20%. Results showed the metal concentration of Cd, Cr, Fe, Mo, Mn, Ni and Pb were reduced to significant levels as compared with World Health Organization (WHO) standard limits and ground water quality standards (GWQS). Concrete containing fungal (Aspergillus niger and Eupenicillium crustaceum) treated WFS showed increase in compressive strength and decrease in water absorption and porosity in concrete made fungal treated WFS as compared to concrete made with untreated WFS. Results showed that the treatment of WFS by Eupenicillium crustaceum is more effective than Aspergillus niger in the case of metal leaching and improvement of concrete properties. X-ray diffraction (XRD) showed some extra peaks of calcium aluminum silicate hydrate (Gismondine) in concrete containing fungal treated WFS as compared to concrete containing untreated WFS. The strength improvement was due to microbially induced mineral formed by fungi often referred as ‘calcified filaments’ confirms by scanning electron microscopy (SEM) and energy dispersive spectrum (EDS). This ability of fungal culture to form the biomineral results in improvement of concrete properties. Results showed that there was better enhancement in strength properties at 20% replacement of fine aggregate with fungal (Eupenicillium crustaceum) treated WFS as compared to concrete made with untreated WFS.
PHD, DBTES
Keywords: fungi; metal leaching; microbial concrete; solid waste management; SEM; WFS; XRD